Triatoma infestans bugs in Southern Patagonia, Argentina - Piccinali, Romina Valeria (2010)
We report the unprecedented finding of a Triatoma infestans bug in Southern Patagonia, initially attributed to accidental transport by Bolivian immigrants. However, molecular analysis showed the bug to have a COI haplotype found only in Argentina, and to be related phylogenetically to other Argentinean haplotypes and not to Bolivian ones.